2010
DOI: 10.1592/phco.30.10.1004
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Glomerular Filtration Rate by Using Serum Cystatin C and Serum Creatinine Concentrations in Patients with Human Immunodeficiency Virus

Abstract: The MDRD equation and the equation that included both serum cystatin C and creatinine concentrations appear to provide accurate, precise, and relatively unbiased estimates of GFR in patients with HIV. Larger studies are needed that include patients with muscle wasting and lipodystrophy in order to validate these preliminary observations and the effects of body composition on the predictability of GFR with use of these equations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 19 publications
1
15
0
Order By: Relevance
“…Prior studies comparing various GFR-estimating equations to an exogenous indicator of GFR have shown that both eGFR SCR and eGFR CYSC are considerably biased (−10 to −29 mL/min/1.72 m 2 ) in HIV-infected persons (31). Moreover, Barraclough and colleagues demonstrated that cystatin C-based estimates of kidney function were less accurate than those based on serum creatinine, with 41% versus 89% falling within 30% of the measured GFR, respectively (31,32). These studies, however, consisted of no more the 30 participants, limiting their generalizability to the HIV-infected population at large.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies comparing various GFR-estimating equations to an exogenous indicator of GFR have shown that both eGFR SCR and eGFR CYSC are considerably biased (−10 to −29 mL/min/1.72 m 2 ) in HIV-infected persons (31). Moreover, Barraclough and colleagues demonstrated that cystatin C-based estimates of kidney function were less accurate than those based on serum creatinine, with 41% versus 89% falling within 30% of the measured GFR, respectively (31,32). These studies, however, consisted of no more the 30 participants, limiting their generalizability to the HIV-infected population at large.…”
Section: Discussionmentioning
confidence: 99%
“…15 While most laboratories use the MDRD equation to calculate eGFR, neither the MDRD nor the CKD-EPI have been well validated in Black patients with a broad spectrum of HIV severity. [16][17][18][19] Furthersearch question using the outcome of all-cause mortality as a surrogate for chronic kidney disease as CKD has been shown to be strongly associated with death [22][23][24][25] in a national registry of HIV-infected veterans. Specifically, we evaluated the impact of removing the race coefficient from the MDRD and CKD-EPI equations on comparisons between Black and White HIV-infected veterans related to: 1) the prevalence of reduced eGFR; 2) the distribution of eGFR values; and 3) the relationship between eGFR and all-cause mortality.…”
Section: Racial Disparities In Estimating Gfr -Anker Et Almentioning
confidence: 99%
“…This equilibrium is the basis for the calculation of the surface tension/surface energy components, and some models such as the Owens-Wendt-Rabel-Kaelble method (OWRK) (Owens and Wendt 1969;Kaelble 1970) distinguish a polar and a disperse fraction of the surface energy. The surface energy was calculated by exploiting the contact angle values (Cappelletti et al 2013).…”
Section: Sample Characterizationmentioning
confidence: 99%